The Impact of Religious Connectedness on Health-Related Quality of Life in Patients with Diabetic Foot Ulcers - Alzahrani, Hasan Ali (Journal of religion and health, 2013)
Religious connectedness is common phenomenon in Saudi Arabia and adjacent Gulf countries. An observational case control study was designed, enrolling 180 adult patients to report the association between religious connectedness and health-related quality of life (HRQL) in people with and without diabetes and foot ulcers. Sixty diabetic patients with foot ulcers (Group I) were compared with sixty diabetic patients without foot ulcer (Group II) and sixty healthy subjects (Group III) for assessment of their HRQL by using SF-36 questionnaire. The effect of religious connectedness was assessed using intrinsic/extrinsic religious connectedness scale. HRQL was found to be significantly lower in Group I compared with Group II and III as well as in group II compared with group III (P < 0.001). Group I patients showed a poorer HRQL with increased severity, duration and multiplicity of foot ulcers. There was a strong positive relationship between religious connectedness and HRQL as indicated by a positive correlation between religious connectedness scale and mental, physical component summary scores (r = 0.66 and 0.59 respectively and P < 0.001). While quality of life is generally poor in people with diabetic foot ulcers, there exists a strong positive relationship between religious connectedness and higher HRQL. These findings may have implications on improving outcomes.